Prototipe Stasiun Penukaran Baterai Kendaraan Listrik Umum (SPBKLU) Ringan Berbasis Energi Surya untuk Sepeda Listrik - Richad Syahputra Sihombing; Rishal Asri; Rihardian Maulana Wicaksono; Guna Bangun Persada; Koko Friansa (P3M Politeknik Negeri Cilacap, 2026)
The transition to electric vehicles in Indonesia continues to progress, along with increasing awareness of the importance of reducing emissions and utilizing renewable energy. One of the challenges still faced is the limited infrastructure for charging and battery swapping. This study designed a battery charging system using two 100Wp solar panels connected in parallel to increase the charging current, and a Maximum Power Point Tracking solar charge controller to regulate the input current to the battery. Tests were conducted on three variations of battery capacity, namely one battery (12 Ah), two batteries (24 Ah), and four batteries (48 Ah), to evaluate the efficiency and charging time of the batteries. The results showed that the charging time for each variation ranged from 3 to 6 hours, depending on the number of batteries and solar irradiation conditions. The designed lightweight Public Electric Vehicle Battery Charging System (SPBKLU) proved to be a sustainable emergency solution for battery charging using renewable energy sources.